Managing the Market Portfolio - Hollstein, Fabian; Prokopczuk, Marcel (Management Science, 2023)
We analyze the relation between time-series predictability and factor investing. We use a large set of financial, macroeconomic, and technical variables to time-series-manage the market portfolio. A combination of the out-of-sample market excess return forecasts of all variables yields a managed market portfolio that generates alphas relative to cross-sectional factor models that exceed 5% per annum. More broadly, the relation between time-series evaluation measures and (multifactor) alphas is weakly positive but complex. The variables’ predictability for future returns is more important than that for volatility. Finally, we document that managed market portfolios based on lagged factor realizations also perform well. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4459 .